VD_FINDINFO Arrêt / 2025 / 40 vom 15. Januar 2025 - VD Tribunal cantonal (2025)
AC, RESTITUTIONEN GÉNÉRAL, REJET DE LA DEMANDE, PROCÉDURE SOMMAIRE | 95 al. 1 LACI, 25 al. 1 LPGA, 51 LPGA, 53 al. 1 LPGA, 53 al. 2 LPGA, 4 al. 4 OPGA